The Girl Who Hated Ponies - Betancourt, Jeanne; Illustrated by Bachem, Paul (New York Scholastic Inc., 1997)
Melissa Prince is spending a weekend with the Pony Pals, but she cares only about her hair and her clothes and claims to hate ponies! But a surprise snowstorm and a pony makeover party will bring many changes--and a new Pony Pal.
Include illustrations
Keywords: Ponies -- Friendship